1984
DOI: 10.1159/000158530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Gradient on the Rate of Relaxation of Rat Mesenteric Small Arteries from Potassium Contractures

Abstract: We have measured the relaxation of rat mesenteric small arteries (internal diameter ca. 200 µm) from a potassium contracture under conditions where the transplasmalemmal sodium gradient was altered. Adjustment of the sodium gradient was made either by exposing vessels to ouabain (1 mM) for different periods to vary the intracellular sodium concentration (Nai), or by varying the sodium concentrations of the relaxation solutions (Nao). Under normal conditions (where we have previously shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Indeed, the data suggest that relatively small changes in A/iNa may alter the contractility of vascular smooth muscle by altering the sarcoplasmic reticulum stores of Ca2+, even though they do not affect tonic tension. The fact that similar effects are seen with low doses of ouabain in rat mesenteric small arteries (Aalkjaer & Mulvany, 1985) casts doubt on the view that 'small changes in sodium gradient have little effect on calcium metabolism of (these) arteries' (Petersen & Mulvany, 1984). The aforementioned tension measurements provide only indirect information about the influence of A#.Na on [Ca2+]i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the data suggest that relatively small changes in A/iNa may alter the contractility of vascular smooth muscle by altering the sarcoplasmic reticulum stores of Ca2+, even though they do not affect tonic tension. The fact that similar effects are seen with low doses of ouabain in rat mesenteric small arteries (Aalkjaer & Mulvany, 1985) casts doubt on the view that 'small changes in sodium gradient have little effect on calcium metabolism of (these) arteries' (Petersen & Mulvany, 1984). The aforementioned tension measurements provide only indirect information about the influence of A#.Na on [Ca2+]i.…”
Section: Resultsmentioning
confidence: 99%
“…on arterial smooth muscle relaxation has been investigated in a few studies, (e.g. Bohr et al 1969;Petersen & Mulvany, 1984). The fact that relaxation from low-Na+ contractures was inhibited only when most of the external Na+ was removed has raised questions about the physiological significance of Na-Ca exchange in this tissue (e.g.…”
mentioning
confidence: 99%
“…Recent topological analyses suggest that the NCX1 protein consists of nine transmembrane segments and a large central cytoplasmic loop, as illustrated in Fig. 1 (35, 38, (6,69,71). Nevertheless, some other reports suggest that Na ϩ /Ca 2ϩ exchange plays little role in cellular Ca 2ϩ homeostasis because of the relatively low activity of the vascular Na ϩ /Ca 2ϩ exchanger compared with other electrically excitable tissues (7,13,64).…”
Section: Early Studies On the Role Of Endogenous Cardiotonic Steroidsmentioning
confidence: 99%
“…[8][9][10][11][12][13] Similarly, pharmacological inhibition of NCX slows the relaxation of agonistevoked contraction and increases agonist-evoked contraction in systemic vascular muscle tissues. 8,9,[13][14][15][16][17][18][19][20][21][22] In addition, NCX may function in the reverse mode to cause or facilitate extracellular Ca 2+ influx in systemic vascular SMCs and to enhance agonist-induced contraction in systemic vascular tissues. [23][24][25][26][27] Consistent with the established importance of NCX1 in systemic vascular SMCs, a number of studies have shown that the hypertension is associated with changes in the activity of NCX in various types of arterial beds.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of NCX by replacing extracellular Na + with Li + or using antisense oligonucleotides‐mediated gene knockdown significantly delays the removal of the elevated [Ca 2+ ] i following application of agonists and enhances agonist‐induced increases in [Ca 2+ ] i in systemic vascular SMCs 8–13 . Similarly, pharmacological inhibition of NCX slows the relaxation of agonist‐evoked contraction and increases agonist‐evoked contraction in systemic vascular muscle tissues 8,9,13–22 . In addition, NCX may function in the reverse mode to cause or facilitate extracellular Ca 2+ influx in systemic vascular SMCs and to enhance agonist‐induced contraction in systemic vascular tissues 23–27 .…”
Section: Introductionmentioning
confidence: 99%